Change of moraine-dammed glacial lakes and simulation of glacial lake outburst flood in the Yi’ong Zangbo River basin - Wang, Qi; Duan, Hongyu; Liu, Na; Du, Zhishui; Wang, Pan; Yi, Bo; Xu, Jun; Huang, Jian; Zhang, Yuan; Yao, Xiaojun (Frontiers in Earth Science, 2022)
Glacial lake outburst floods (GLOFs) are a serious potential threat to the safety of life and property in downstream areas. In this study, moraine-dammed glacial lakes in the Yi’ong Zangbo River basin were recognized based on Landsat ETM+/TM/OLI images in 2000 and 2019. And the GLOFs for the Jionglaco, the largest glacial lake in this basin, was simulated using the one-dimensional hydrodynamic model. The results show that the total number and area of moraine-dammed glacial lakes in this basin increased by 10 (10.52%) and 5.49 km2 (48.24%) from 2000 to 2019, in which the area of the Jionglaco increased by 3.22 km2. The peak discharge at the breach outlet for five scenarios with different combinations of breach width (80 m and 120 m), depth (2.5 m and 5 m) and flood time (1.5 h and 3 h) are 489 m3/s, 1327.43 m3/s, 444.32 m3/s, 617.47 m3/s and 1570.61 m3/s. With the addition of baseflow in river, the peak discharge at bridge site 15 138.93 km from Jionglaco are 1040.89 m3/s, 1724.00 m3/s, 1024.85 m3/s, 1162.25 m3/s and 1990.52 m3/s. The combination of baseflow in river and the GLOFs discharge results in the increasing peak discharge in the further downstream region. However, the arrival of peak discharge in downstream areas is delayed, which increases the chances of people escaping.